Integrasi QRIS dan Pencatatan Digital: Efektivitas Pengelolaan Keuangan UMKM Primavera Catering - Hasya Ramaniya Yumna; Ratri Paramitalaksmi (-, 2026)
Micro, small, and medium enterprises (MSMEs) in Indonesia continue to rely on cash and manual bookkeeping, exposing them to recording errors, transaction inefficiency, and weak cash-flow monitoring. This community service activity aimed to strengthen the financial management effectiveness of Primavera Catering, a home-based catering MSME in Yogyakarta, by integrating the Quick Response Code Indonesian Standard (QRIS) as a digital payment channel with the Buku Kas digital bookkeeping application. The intervention followed a participatory assistance approach comprising field observation, in-depth interviews, problem identification, solution design, hands-on mentoring, and evaluation. The results indicate that QRIS implementation shortened transaction time, broadened payment options, and improved payment traceability, while structured digital bookkeeping enabled the owner to record, classify, and monitor cash inflows and outflows more accurately; during the observation period the business recorded cash inflows of Rp18,311,000 and outflows of Rp11,083,500, yielding a closing balance of Rp7,227,500. The dual intervention improved recording accuracy, financial transparency, and the owner's digital financial literacy, supporting more informed and sustainable business decisions. The findings suggest that integrating digital payment and digital bookkeeping is a low-cost, replicable strategy for accelerating MSME financial digitalization.